Land Cover Change and Carbon Potential in Mangrove Ecosystems at The Social Forestry Area (Study Case: Indramayu Regency, Indonesia) - Pelawi, Rospita Br; Panuju, Dyah Retno; Rusdiana, Omo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
This study investigates land cover change and carbon potential in mangrove ecosystems within the social forestry area of Indramayu Regency. The research aims to assess land cover changes from 2014 to 2020 and estimate the carbon potential stored in mangrove ecosystems. Field surveys and satellite images analyze land cover change patterns and quantify mangrove carbon storage potential. The research findings reveal that aquaculture land cover dominates the study area (reaching 90%). The study did not find significant changes in land cover within the social forestry area. Only minor changes were noted, with mangroves converting to aquaculture and vice versa. The carbon potential is obtained from biomass calculated based on tree diameter within the research area. According to the calculations, it was found that the three research areas have different potentials due to varying tree diameters and densities. The carbon potential from thepermitted areas of Karya Wana Tiris, Babadan Lestari, and Hijau Mandiri are 24.54 tons, 18.33 tons, and 24.87 tons. The highest carbon potential occurred in 2020 (2,419.69 tons), while the lowest was in 2017 (1,414.06 tons).